Complex neural representation of odour information in the olfactory bulb. (2nd July 2019) - Li, Anan; Rao, Xiaoping; Zhou, Yang; Restrepo, Diego
Abstract: The most important task of the olfactory system is to generate a precise representation of odour information under different brain and behavioural states. As the first processing stage in the olfactory system and a crucial hub, the olfactory bulb plays a key role in the neural representation of odours, encoding odour identity, intensity and timing. Although the neural circuits and coding strategies used by the olfactory bulb for odour representation were initially identified in anaesthetized animals, a large number of recent studies focused on neural representation of odorants in the olfactory bulb in awake behaving animals. In this review, we discuss these recent findings, covering (a) the neural circuits for odour representation both within the olfactory bulb and the functional connections between the olfactory bulb and the higher order processing centres; (b) how related factors such as sniffing affect and shape the representation; (c) how the representation changes under different states; and (d) recent progress on the processing of temporal aspects of odour presentation in awake, behaving rodents. We highlight discussion of the current views and emerging proposals on the neural representation of odorants in the olfactory bulb.